Odpowiedź :
Odpowiedź:
a)(-x+2)(4-3x) - 3(x+1)² = -4x + 3x² + 8 - 6x -3(x²+2x+1) = -10x + 3x² + 8 - 3x² - 6x - 3 = -16x + 5
dla x = (-2)
-16x + 5 = -16 * (-2) + 5 = 32 + 5 = 37
b) (2a+1)(a²-a-1) - 2(a² + 1)(a-1) = 2a³ - 2a² - 2a + a²- a - 1 - 2(a³ - a² + a -1) = 2a³ - a² - 3a - 1 -2a³ + 2a² - 2a + 2 = a² - 5a + 1
dla x = [tex]\sqrt{3}[/tex]
a² - 5a + 1 = [tex]\sqrt{3}[/tex]² - 5
Odpowiedź:
a)
(-x + 2)(4 - 3x) - 3(x + 1)² = (2 + 2)(4 + 6) - 3(-2 + 1)² = 4 * 10 - 3(-1)² = 40 - 3 = 37
dla
x = (-2)
b)
(2a + 1)(a² - a - 1) - 2(a² + 1)(a - 1) = (2√3 + 1)(3 - √3 - 1) - 2(3+ 1)(√3 - 1) =
= (2√3 + 1)(2 - √3) - 2*4(√3 - 1) = 4√3 - 2*3 + 2 - √3 - 8√3 + 8 = -5√3 - 6 + 10 = -5√3 + 4
dla
a = √3
Szczegółowe wyjaśnienie: